Integrating Dayak Local Wisdom Values into Christian Religious Education as a Model for Contextual Learning - Perminas Duatan; Yanet Rannu; Marson Apui (CV. Publikasi Indonesia, 2026)
This study examines the integration of Dayak local wisdom values into Christian Religious Education as a contextual learning model. The study is motivated by the need for Christian education that is capable of responding to globalization and digital transformation while remaining rooted in local cultural identity. This research uses a qualitative descriptive method with a literature study approach by examining various books, scientific journals, and academic articles related to Dayak culture, contextual learning, and Christian Religious Education. The results show that Dayak local wisdom contains educational values such as mutual cooperation, solidarity, respect for nature, communal life, responsibility, and spirituality that are relevant to the principles of Christian Religious Education. These values can be integrated into contextual learning through teaching materials, character education, learning strategies, and reflective learning experiences based on students’ cultural backgrounds. The integration of Dayak local wisdom into Christian Religious Education not only creates meaningful and contextual learning but also contributes to character formation, strengthening cultural identity, and fostering ecological awareness among students. Therefore, Dayak local wisdom has significant potential to be developed as a contextual learning model in Christian Religious Education.